Pengembangan Modul Donatur pada Aplikasi SiKembar Berbasis Web untuk Meningkatkan Efektivitas Pengelolaan Donasi dan Interaksi Pengguna - Samuel Torang Sitorus; Isram Rasal (Asosiasi Profesi Telekomunikasi Dan Informatika Indonesia, 2025)
This research discusses the development of a donor module on the SiKembar (Barang Entry and Exit Information System) web-based application, designed to optimize the management of donor data and donation aid during natural disasters. The module is developed to facilitate the donation submission process from the public, ultimately aiming to improve coordination between the community, government, and BPBD (Regional Disaster Management Agency) of Cianjur Regency in managing and distributing post-disaster aid. The development method used in this module is web-based, utilizing PHP programming language and the CodeIgniter framework. The CodeIgniter framework was chosen for its ease of use in building structured and flexible web applications. The donor module developed is integrated into the existing SiKembar platform, allowing for more efficient and organized donor data management. The main feature introduced in this module is the donation submission, which enables the public to directly donate and track the status of their submitted donations through the platform. The results of the research indicate that this module facilitates a more structured and responsive donation submission process. Both donors and administrators can easily access and manage information related to the aid needed and the status of received donations. This enhances transparency and efficiency in donation data management while minimizing the potential for errors in aid distribution. The donor module on the SiKembar application is expected to increase the effectiveness of managing donor data and handling aid following natural disasters. With this system, the aid distribution process will be more organized and faster, while also facilitating better coordination among the involved parties. Ultimately, this module can contribute to accelerating post-disaster recovery and ensuring that aid reaches those in need in a timely manner.